2012
DOI: 10.1210/me.2012-1101
|View full text |Cite
|
Sign up to set email alerts
|

Dopamine-Mediated Autocrine Inhibitory Circuit Regulating Human Insulin Secretion in Vitro

Abstract: We describe a negative feedback autocrine regulatory circuit for glucose-stimulated insulin secretion in purified human islets in vitro. Using chronoamperometry and in vitro glucose-stimulated insulin secretion measurements, evidence is provided that dopamine (DA), which is loaded into insulin-containing secretory granules by vesicular monoamine transporter type 2 in human β-cells, is released in response to glucose stimulation. DA then acts as a negative regulator of insulin secretion via its action on D2R, w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

8
105
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 76 publications
(113 citation statements)
references
References 68 publications
8
105
0
Order By: Relevance
“…The other likely possibility is paracrine control of islet blood flow arising from products secreted from the islet cells. Three possible molecules that can control vasodilation (6,10,13,15,19,21,22,27,56) and are known to be associated with insulin secretion are nitric oxide (NO), ATP/adenosine, and dopamine (23,31,34,48,51,54). Because the control of islet blood velocity needs to occur upstream of the ␤-cells, paracrine control must also occur upstream.…”
Section: E328 Connexin 36 Mediates Blood Cell Flow In Isletsmentioning
confidence: 99%
See 1 more Smart Citation
“…The other likely possibility is paracrine control of islet blood flow arising from products secreted from the islet cells. Three possible molecules that can control vasodilation (6,10,13,15,19,21,22,27,56) and are known to be associated with insulin secretion are nitric oxide (NO), ATP/adenosine, and dopamine (23,31,34,48,51,54). Because the control of islet blood velocity needs to occur upstream of the ␤-cells, paracrine control must also occur upstream.…”
Section: E328 Connexin 36 Mediates Blood Cell Flow In Isletsmentioning
confidence: 99%
“…This residual glucose-dependent velocity increase is due at least partially to central nervous system signaling (24) coupled with the potential paracrine signal from islet ␤-cells. Because the release of paracrine mediators likely corresponds to insulin secretion from the ␤-cells (23,31,34,48,51,54), we would expect differences in their temporal profile, although their total level may be unchanged as a function of Cx36 expression (18). Such a paracrine signal(s) would putatively control local blood cell velocity via transmission to arterioles immediately adjacent to islets.…”
Section: E328 Connexin 36 Mediates Blood Cell Flow In Isletsmentioning
confidence: 99%
“…Recent studies have shown that molecules involved in dopamine receptor signaling are expressed not only in the brain but also in both murine and human pancreatic islets [52, 53]. In patients with Parkinson’s disease, treatment with l -DOPA, a dopamine precursor, significantly impairs glucose metabolism in a dose-dependent manner [54, 55].…”
Section: Impact Of a Brown Rice-derived Bioactive Product On Feeding mentioning
confidence: 99%
“…A study done recently has shown a negative feedback regulatory circuit for glucose-stimulated insulin secretion in purified human islets in vitro [19] . The release of dopamine and insulin together in response to the glucose load is demonstrated by the in-vitro infusion of dopamine into the insulin-containing secretory granules of human β-cells.…”
Section: +mentioning
confidence: 99%
“…The release of dopamine and insulin together in response to the glucose load is demonstrated by the in-vitro infusion of dopamine into the insulin-containing secretory granules of human β-cells. Dopamine in turn exerts an antagonistic action on the D2 receptors that are also expressed on β-cells and thus inhibiting insulin secretion [19] . Neuroendocrine cells and pancreatic islets take up L-DOPA and convert it into Dopamine by the enzyme DOPA decarboxylase, which is expressed in β-cells of the pancreatic islets [20][21][22][23] .…”
Section: +mentioning
confidence: 99%